Spectinamides are effective partner agents for the treatment of tuberculosis in multiple mouse infection models. (13th December 2016) - Robertson, Gregory T.; Scherman, Michael S.; Bruhn, David F.; Liu, Jiuyu; Hastings, Courtney; McNeil, Michael R.; Butler, Michelle M.; Bowlin, Terry L.; Lee, Robin B.; Lee, Richard E.; Lenaerts, Anne J.
Abstract : Objectives: New drug regimens employing combinations of existing and experimental antimicrobial agents are needed to shorten treatment of tuberculosis (TB) in humans. The spectinamides are narrow-spectrum semisynthetic analogues of spectinomycin, modified to avoid intrinsic efflux by Mycobacterium tuberculosis . Spectinamides, including lead 1599, have been previously shown to exhibit a promising therapeutic profile in mice as single agents. Here we explore the in vivo activity of lead spectinamides when combined with other agents. Methods: The efficacy of 1599 or 1810 was tested in combination in three increasingly advanced TB mouse models. Mice were infected by aerosol and allowed to establish acute or chronic infection, followed by treatment (≤4 weeks) with the spectinamides alone or in two- and three-drug combination regimens with existing and novel therapeutic agents. Bacteria were enumerated from lungs by plating for cfu. Results: Herein we show the following: (i) 1599 exhibits additive or synergistic activity with most of the first-line agents; (ii) 1599 in combination with rifampicin and pyrazinamide or with bedaquiline and pyrazinamide promotes significantly improved efficacy in the high-dose aerosol model; (iii) 1599 enhances efficacy of rifampicin or pyrazinamide in chronically infected BALB/c mice; and (iv) 1599 is synergistic when administered in combination with rifampicin and pyrazinamide in the C3HeB/FeJ mouse model showing caseous necrotic pulmonary lesions. Conclusions: Spectinamides were effective partner agents for multiple anti-TB agents including bedaquiline, rifampicin and pyrazinamide. None of these in vivo synergistic interactions was predicted from in vitro MIC chequerboard assays. These data support further development of the spectinamides as combination partners with existing and experimental anti-TB agents.